Ethanol Extract Turmeric (Curcuma domestica val) In Preventing an Increased Grastic Acidity on Rattus norvegicus Which Induced by Histamine - Nugroho Eko Wirawan Budianto (Universitas Wijaya Kusuma Surabaya, 2014)
Gastric ulcer is one of the increase gastric acid causes which mediated by H2 reseptor. Tumeric is extracted using the ethanol 96% and it is tested using Rattus norvegicus Wistar strain to know the effect as anti gastritis. There’s a suspicion whether an ethanol extraction from tumeric which has anti H2 receptor effect can be use to prevent gastric ulcer causes from histamine release. Based on that, we want to study whether tumeric can be use to prevent the increase of histamine induce gastric acid and can also be use as gastric protective by looking at microscopic image of gastric, gastric pH from Rattus norvegicus Wistar strain.Methods: Male Wistar rats were divided Into five groups: 1) Na CMC control group, 2) CMC Na io histamine plus 300 mg / kg ip groups, 3) ethanol turmeric extract 1000 mg / kg io histamine plus 300 mg / kg ip treated groups, 4) ethanol turmeric extract 2000 mg / kg io histamine plus 300 mg / kg ip treated groups. Rats were sacrified at 6 h after injection of histamine, and stomach tissues were harvested for free acid, total acid, organic acid, pH.Results: Giving P2 ethanol extract of tumeric intra oral decrease free acid level, total acid, organic acid and pH gastric acid which is induced by giving an intra peritoneal histamin. Ethanol extract of tumeric decrease incidence and preventable for ulcus gastric causes by histamin.Conclusion: an ethanol extract of tumeric decrease the levels of free acid, total acid, organic acid and pH gastric. Ethanol tumeric extract 2000 mg/kg is a recommended dosage